2010
DOI: 10.1111/j.1445-5994.2009.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in secondary stroke prevention: prevalence of multiple metabolic risk factors, including abnormal glycaemia, in ischaemic stroke and transient ischaemic attack

Abstract: Abnormal glycaemia was present in almost half the patients presenting with IS/TIA, with the majority of cases undiagnosed. One-third of patients had abnormal glycaemia, hypertension and dyslipidaemia concurrently. Patients presenting with stroke should be routinely screened for abnormal glycaemia in concert with other vascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Serum CRP levels are well studied as sensitive circulating markers of inflammation, as CRP is independently associated with an increased risk of cardiovascular disease and diabetes (18)(19)(20)(21)(22). In addition to these previous associations, our study identifies new information regarding CRP and disease outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…Serum CRP levels are well studied as sensitive circulating markers of inflammation, as CRP is independently associated with an increased risk of cardiovascular disease and diabetes (18)(19)(20)(21)(22). In addition to these previous associations, our study identifies new information regarding CRP and disease outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…A retrospective audit from a tertiary Sydney metropolitan hospital found 25% of IS/TIA patients had pre-existing DM, while 10% of them had newly diagnosed DM based on fasting and/or random plasma glucose. 24 In a recent prospective observational study conducted in Melbourne, 26% of stroke patients had pre-existing DM, and 4.9% were newly diagnosed based on an admission HbA1c value of ≥6.5%. 25 This observed increased prevalence of DM in strokes correlates with the rising proportion of diabetic patients in the general Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Their data showed that stress hyperglycaemia and newly diagnosed DM conferred a poor prognosis. A retrospective audit from a tertiary Sydney metropolitan hospital found 25% of IS/TIA patients had pre‐existing DM, while 10% of them had newly diagnosed DM based on fasting and/or random plasma glucose 24 . In a recent prospective observational study conducted in Melbourne, 26% of stroke patients had pre‐existing DM, and 4.9% were newly diagnosed based on an admission HbA1c value of ≥6.5% 25 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, 67% to 85% of patients with stroke stop treatment within 3 months of discharge. 9 After stroke onset, 46.2% of these patients do not take the required medication. 10 In addition, after diagnosis, more than 25% of stroke patients engage in smoking, drinking alcohol, noncompliance with a low-salt diet, or insufficient physical activity.…”
mentioning
confidence: 99%
“…Self-management decreases the risk of recurrent vascular events in patients with stroke by approximately 80% or more and reduces hospital admission and mortality 7,8 . However, 67% to 85% of patients with stroke stop treatment within 3 months of discharge 9 . After stroke onset, 46.2% of these patients do not take the required medication 10 .…”
mentioning
confidence: 99%